It is not worth postponing frozen embryo transfers after oocyte pickup: A retrospective cohort study based on propensity score matching - Ji, Mengxia; Jin, Bihui; Guo, Xiaoyan; Wu, Ruifang; Jiang, Yunqing; Zhang, Ling; Shu, Jing (Frontiers in Endocrinology, 2022)
This study was to explore whether postponing frozen embryo transfers (FET) after oocyte pickup (OPU) improves clinical and neonatal outcomes. From May 2018 to Dec 2020, a total of 1109 patients underwent their first OPU cycles adopting a non-selective freeze-all policy were included in this retrospective cohort study. In the immediate group (n=219), patients underwent FET in the first menstrual cycle after OPU, and patients in the postponed group (n=890) waited for more than 1 menstrual cycle after OPU to perform FET. A propensity score matching (PSM) model was used to evaluate the clinical outcomes and neonatal outcomes between the two groups. There were 209 patients in the immediate group and 499 patients in the postponed one after PSM. Patients waited for a significantly shorter period for FET in the immediate group (30.74 ± 3.85 days) compared with the postponed group (80.39 ± 26.25 days, P<0.01). The clinical pregnancy rate (CPR) and live birth rate (LBR) in the immediate group were 58.4% and 48.3%, respectively, which were comparable to those of the postponed one (58.1%, 49.7%, P > 0.05). No statistical significance was found in the average birth weight (3088.82±565.35 g vs 3038.64±625.78 g, P > 0.05) and height (49.08±1.87 cm vs 49.30±2.22 cm) of neonates between the two groups. The gender ratio, the incidence of macrosomia and low birth weight did not differ significantly between the two groups. In conclusion, postponing FET does not improve clinical and neonatal outcomes. If patients have no contraindications, FETs should be carried out immediately after OPU.